Age-specific performance tests in ski biathlon with database application - Zebzeev, V. V.; Zdanovich, O. S. (Fiziceskaja Kultura: vospitanie, obrazovanie, trenirovka, 2017)
The study considers the matters of age-specific performance tests in ski biathlon using a special database. Subject to the study were 96 ski biathlon competitors of 11-12 years of age in the 3rd year training stage; the 16-17 years-old racing skiers in the 5th year training stage; and the 19-20 years-old racing skiers in the sport excellence stage. The special sport database was designed to include six data modules such as the athletes` anthropometrics; most important competitive progress rates; technical, physical and performance rates of the racing skiers and their variations for the current competitive season in particular and the Olympic cycle on the whole. It is the athletes` model technical, physical, performance and competitive fitness rates that comprise the key components of the database. It was via the active application of the Performance Rating Module of the database and the actual test rates being managed versus the model rate that the Study Group coaching team designed the optimal training systems for the age- and qualification-specific subgroups for the study period; and the experimental system benefits were verified by the performance tests of the subject racing skiers.